The role and involvement of NGOs in activities related to humanitarian issues in Palestine - al-Modallal, Isra; Bahar, Ahmad; Lee, Jess (International Journal of Multidisciplinary Approach Research and Science, 2023)
The colonialism and tyranny of the Palestinian people after the silence of the large-scale countries and the limited support of the Palestinian National Authority or the rather westernized capacity of the people, the presence of various types of non-governmental organizations or non-governmental organizations (NGOs) carries out humanitarian assistance activities for vulnerable groups. This. The main objective of this research is to recognize the nature of humanity and the contribution of Malaysian Humanitarian NGOs to the Palestinian Humanitarian issue. Based on a qualitative approach, a virtual meeting was held with three members of the Safe Palestine NGO. The selection of this NGO was based on special assistance to the Palestinians and active involvement since the establishment of the organization. The study shows that there are various forms of assistance for humanity, Safe Palestine, through projects involving the economic, educational, social, health, agricultural, and infrastructure sectors that have successfully contributed to the health of people in the world. Active involvement through activities in Malaysia has made awareness of the Palestinian issue among the Malaysian community. However, Safe Palestine projects and activities are considered to be religious. The essence of the Palestinian issue is equated as humanism and not religion solely so that all ethnic groups, regardless of religious background, can go hand in hand in refuting Israel's misanthropy.